A comprehensive framework and associated methodology for the design, operative planning, and operation of district heating systems to facilitate the transition towards a fully renewable heat supply - Peter Lorenzen (Universitat Politècnica de València, 2022)
District heating systems (DHSs) are a mature technology for an efficient heat supply in cities. In the context of the climate crisis and the related goal of a decarbonized heating sector, DHSs play an ambivalent role. As existing DHSs are mostly based on fossil fuels, they are part of the problem. However, as they can also integrate renewable heating plants, DHSs offer a great potential to support the transition towards a fossil-free heat supply. This transition is hindered by several barriers. For example, low supply temperatures are needed for the economically efficient integration of renewable heating plants. However, since existing fossil heating plants marginally benefit from a reduction of the temperature, a lock-in effect to the established business models exists. In the current research, resolving the barriers is focused either on individual solutions for specific issues or on heat strategies for a general level. Since the barriers are strongly interrelated, district heating (DH) companies require a systemic transition methodology for their specific activities in the different fields of planning and operation. Since such a transition methodology is identified as lacking in the literature, this thesis aims to develop a comprehensive methodology that facilitates the transition in an economically efficient way. To develop such a transition methodology, this thesis introduces a framework approach that combines new and existing independent concepts and that is built on a newly developed structure of eight "DH scopes." These DH scopes classify the activities in the different fields of DH concerns. To address the planning and operation activities in DH companies, these activities are integrated into the new "framework" that is classified according to the three DH scopes "design," "operative planning," and "operation." The framework summarizes the related activities according to processes and links them using technical and economic mechanisms. These mechanisms are considered in such a way that all activities are incentivized to facilitate the transition. A new organizational structure is proposed that allows for the introduction of competition while the framework secures so-called suboptimization, abuse of market power, or investment restraint. Independent heat producers are integrated in a system-serving way. The framework integrates the relevant technologies that offer flexibility to the system to compensate for fluctuation in production. In this thesis, a framework is devised that is suitable for implementing a comprehensive "transition paradigm" to existing or future DHSs. Further, it can be used by policymakers or municipalities to improve existing legal conditions and local heat strategies in relation to a comprehensive overall system. The thesis recommends further investigation for the implementation of the framework and a quantitative evaluation of the introduction of competition to DHSs.
Keywords: District heating; Renewable heating plants; Thermal flexibility; Heat markets; Thermal systems